2023
DOI: 10.1002/nur.22302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on obstructive sleep apnea–hypopnea syndrome: A meta‐analysis

Abstract: Our study aimed to systematically evaluate the effect of acupuncture in patients with obstructive sleep apnea-hypopnea syndrome (OSAHS). Literature search of four Chinese databases and six English databases for studies published from the inception of each database to March 1, 2022 and identify relevant studies published in Chinese or English. Related randomized controlled trials of acupuncture for the treatment of OSAHS were included to analyze the efficacy of acupuncture. Two researchers independently reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…A recent meta-analysis, based on 19 studies involving 1365 participants, revealed statistically significant changes in various indicators, including the apnea-hypopnea index, LSpO 2 , ESS, interleukin-6, tumour necrosis factor-alpha (TNF-α), and nuclear factor-kappa B (NF-κB) (44).…”
Section: Clinical Effect Of Acupuncture On Obstructive Sleep Apneamentioning
confidence: 99%
“…A recent meta-analysis, based on 19 studies involving 1365 participants, revealed statistically significant changes in various indicators, including the apnea-hypopnea index, LSpO 2 , ESS, interleukin-6, tumour necrosis factor-alpha (TNF-α), and nuclear factor-kappa B (NF-κB) (44).…”
Section: Clinical Effect Of Acupuncture On Obstructive Sleep Apneamentioning
confidence: 99%
“…Another recent study looked at the effect of acupuncture in patients with obstructive sleep apnea-hypopnea syndrome (OSAHS). 22 Literature search was performed of 4 Chinese databases and 6 English databases for studies published from the inception of each database to March 1, 2022. A total of 19 studies with 1365 participants were examined.…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%
“…obstructive sleep apnea-hypopnea syndrome, cancer-related insomnia) have been proven in other populations. 10,11 Although the number of reports on acupuncture improving sleep quality in Parkinson's disease patients has increased recently, there are few systematic reviews. A recent systematic review of the effects of acupuncture on non-motor symptoms of Parkinson's disease patients that included nine studies on sleep improvement showed that acupuncture benefited Parkinson's disease-related insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…9 According to traditional Chinese medicine, this regulates Yin and Yang through acupoints located on meridians linking peripheral tissues to central organs, providing a link between local and systemic physiology. 10 The safety and efficacy of acupuncture for sleep disorders (e.g. obstructive sleep apnea-hypopnea syndrome, cancer-related insomnia) have been proven in other populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation